Physiological and Pathological Roles of Mammalian NEK7 - Sun, Zhenzhen; Gong, Wei; Zhang, Yue; Jia, Zhanjun (Frontiers in Physiology, 2020)
NEK7 is the smallest NIMA-related kinase (NEK) in mammals. The pathological and physiological roles of NEK7 have been widely reported in many studies. To date, the major function of NEK7 has been well documented in mitosis and NLRP3 inflammasome activation, but the detailed mechanisms of its regulation remain unclear. This review summarizes current advances in NEK7 research involving mitotic regulation, NLRP3 inflammasome activation, related diseases and potential inhibitors, which may provide new insights into the understanding and therapy of the diseases associated with NEK7, as well as the subsequent studies in the future.